Data on juveniles of the common thresher shark, Alopias vulpinus (Bonnaterre, 1788) (Chondrichthyes:Alopiidae), with comments on the distribution of family Alopiidae in Brazil - Gadig, Otto Bismarck Fazzano; Namora, Rafael Cabrera; Motta, Fábio dos Santos (Arquivos de Ciências do Mar, 2017)
This paper presents morphological, color pattern and biological data on juveniles of the common thresher shark, Alopias vulpinus, caught in coastal area of São Paulo State, Southern Brazil. Thirteen specimens caught by gill nets in July 1999 were studied. Twelve of them were caught in Praia Grande City (24º00’S/46º24’W) and one in Peruíbe City (24º19’S/46º59’W). There are few information on juveniles common thresher shark along the Brazilian coast. Previous reports on its geographical distribution refer to adult specimens from oceanic areas of Southern Brazil where juveniles seem to be frequent visitors. According to up-to-date information, there were not confirmed reports of the presence of this species along the Northern coast of Brazil, although its occurrence is expected, since this shark is widely distributed around the oceanic/coastal areas of the world. The capture of several juveniles during a short-time period in a restricted area indicates a grouping behavior among juveniles of this species. Additionally we present data on the distribution of the bigeye thresher shark, Alopias superciliosus along the Brazilian coast, where this species is more commonly reported than A. vulpinus.